عبدالله الطيب المجذوب وتفسيره للقرآن الطريقة والمنهج = 'Abdallah al-tayyeb al-majthub wa tafsirihi lil al-Quran al-Tariqah wa al-manhaj - Ibrahim, Esam Eltigani Mohamed (IIUM Press, 2013)
Abd Allah al-Tayyib al-Majzub is considered one of the eminent figures in contemporary Sudan. He authored numerous books, among the most prominent of them his exegesis of the Qur’an. This book presented the factors that led to the formation of his personality, including the genetic factor, the educational factor, the national and religious factor, his self-esteem, his love for poetry and Bedouin, his attachment to the Holy Quran, and the impact of his British wife on his personality. It also identified the methodology and way Abd Allah al-Tayyib followed in his exegesis of the Qur’an, and discussed the most important drawbacks held against Abd AllÉh al-Ùayyib, which is the colloquial dialect that he used in his tafsÊr. Furthermore, this book also looked at the way of ÑAbd AllÉh al-Ùayyib in his interpretation of the verses pertaining to natural and cosmological phenomena, the verses of jurisprudence, the verses of the names and qualities of Allah (swt), the verses of the Qur’anic narratives and Israelite, as well as the verses concerning eschatological matters. The methodology relied on in this book was the analytic and inductive methodologies. One of the interesting outcomes of this book was that the overall methodology of his tafsÊr depended primarily on dictum from the Qur'an and Sunnah, citied them from the interpretations of ÙabarÊ and QurtubÊ. Furthermore, the book revealed that ÑAbd AllÉh al-Ùayyib utilized the stories of the people of Israel (Israelite) in his tafsÊr, and he rejected the scientific tafsir.